2005
DOI: 10.1007/s11173-005-0019-0
|View full text |Cite
|
Sign up to set email alerts
|

Tetranuclear bismuth complexes Bi4(O)2(O2CC6H2F3-3,4,5)8 � 2C6H6 and Bi4(O)2(O2CC6H2F3-3,4,5)8 � 2C6H4Me2-1,4: Synthesis and structures

Abstract: X-ray diffraction study of tetranuclear organobismuth complexes Bi 4 ( O ) 2 ( O 2 CC 6 H 2 F 3 -3,4,5) 8 · 2η 6 -ë 6 ç 6 and Bi 4 (O) 2 (O 2 CC 6 H 2 F 3 -3,4,5) 8 · 2(ë 6 ç 4 Me 2 -1,4) revealed four Bi atoms connected through the bridging carboxylate ligands and the O atoms. The coordination sphere of the terminal Bi atoms includes the chelate carboxylate ligand and the η 6 -arene molecule. The bridging O atoms are tricoordinated, the distances between the terminal Bi atom and the center of benzene molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 2 publications
2
18
0
Order By: Relevance
“…3-9, with selected bond lengths and angles given in Table 2. The Bi-C aryl bond distances in 1a-1f and 2 are within 2.229(5)-2.242(5) Å range, comparable to those found in other arylbismuth carboxylates [10,[17][18][19][20]. These distances are slightly shorter than the average Bi-C aryl bond distance reported for BiPh 3 , 2.268 Å [17].…”
Section: Resultssupporting
confidence: 74%
“…3-9, with selected bond lengths and angles given in Table 2. The Bi-C aryl bond distances in 1a-1f and 2 are within 2.229(5)-2.242(5) Å range, comparable to those found in other arylbismuth carboxylates [10,[17][18][19][20]. These distances are slightly shorter than the average Bi-C aryl bond distance reported for BiPh 3 , 2.268 Å [17].…”
Section: Resultssupporting
confidence: 74%
“…Major pathways for introduction of the oxido groups during cluster formation include microhydrolysis, ether elimination, and oxidation. [1c, 4] Several bismuth oxido clusters [Bi m O n ] (3 mÀ2 n)+ with surface capping ligands such as hydroxide, [5] alkoxides, [6] aryl oxides, [7] siloxides, [8] carboxylates, [9] and phosphonates [10] were isolated recently by using solvolytic methods. In addition, a few heterometallic bismuth compounds in which metal atoms are connected through oxido bridges [8b, 11] have also been synthesized by similar approaches.…”
mentioning
confidence: 99%
“…In some cases, both solvent coordination as well as dimerization/oligomerization are observed simultaneously. While Deacon et al [24] suggested that PhBi(O 2 CR) 2 tend to undergo rearrangement reactions to Ph 2 Bi(O 2 CR) and Bi(O 2 CR) 3 , stable examples with R ¼ ClCH 2 , [25] C 6 H 2 F 3 -3,4,5 [26], CH(CH 3 )CH 2 GePh 3 [27], and 2-(C 5 H 4 N)CO 2 [11], as well as the sulfosalicylate complexes [PhBi(2-OH-5-SO 3 HeC 6 H 3 CO 2 ) (H 2 O)] ∞ [5], [PhBi(2-OH-5-SO 3 HeC 6 H 3 CO 2 ) EtOH] ∞ [5] are known. Phenylbismuth heterocylic carboxylates have also been reported [28].…”
Section: Resultsmentioning
confidence: 99%
“…The other BieO distances are 2.321(3), 2.330(4) and 2.473 For L ¼ O 2 CCH(Me)CH 2 GePh 3 versus 2.290(4), 2.315(4) and 2.543(4) Å here. [25], and [PhBi(3,4,5-F 3 -C 6 H 2 CO 2 ) 2 ] [26].…”
Section: Resultsmentioning
confidence: 99%